Enhancing Student Self-Confidence through Cognitive Restructuring: A High School Group Guidance Approach - Sitinjak, Niken Viska; Yakub, Elni; Mardes, Siska; Muna, Zurratul (Jurnal Psikologi Terapan, 2023)
The aim of this study was to investigate the effectiveness of cognitive restructuring through group guidance in enhancing students' self-confidence levels. This research investigates the impact of cognitive restructuring through group guidance on enhancing students' self-confidence. The study employed a quasi-experimental design involving a pre-test and post-test assessment to measure changes in self-confidence levels. The participants were eight high school students categorized as having low self-confidence. The intervention involved a six-week group guidance program focusing on cognitive restructuring techniques. The results demonstrated a significant positive correlation between pre-test and post-test self-confidence scores, indicating the intervention's effectiveness in improving self-confidence. The findings highlight the importance of cognitive restructuring as a valuable approach for addressing low self-confidence among students. While the intervention played a pivotal role, it's essential to acknowledge the influence of other internal and external factors in shaping self-confidence.